The association between polymorphisms in miRNA and the cholinesterase activity of workers in an omethoate-exposed environment. Issue 5 (4th May 2022) - Zou, Kaili; Zhou, Xiaoshan; Wang, Wei; Shi, Liuhua; Fu, Xiaoli
ABSTRACT: To explore the association between polymorphisms in microRNAs (miRNAs) and the cholinesterase (ChE) activity in omethoate-exposed workers, we recruited 180 omethoate-exposed workers and 115 controls to measure their ChE activity using acetylcholine and dithio-bis-(nitrobenzoic acid) and genotype susceptible SNPs in their miRNA by time-of-flight mass spectrometry. ChE activity in the exposure group was lower than that in the control group ( P < 0.001). The analysis of covariance result showed that ChE activity was lower in the (- -/- T) genotype in miR-30a rs111456995 (1.97 ± 0.47) than in the TT genotype (2.23 ± 0.59) of the exposure group ( P = 0.004). Multivariate linear regression was performed to find influencing factors on ChE activity, and variables kept in the model included omethoate exposure ( b = −1.094, P < 0.001), gender ( b = −0.381, P < 0.001), miR-30a rs111456995 (- -/- T)( b = −0.248, P < 0.001), and drinking ( b = 0.258, P =0.019). The results suggest that individuals carrying a (- -/- T) genotype in miR-30a rs111456995 were more susceptible to damage in their cholinesterase induced by omethoate exposure.